Dietary Agents and Phytochemicals in the Prevention and Treatment of Hepatocellular Carcinoma: Review Article - Ahmad, Mohammad; Mishra, Anuradha; Usmani, Afreen; Ahmad, Md. Parwez (Med Phoenix, 2017)
Amongst all types of primary liver cancers, hepatocellular carcinoma (HCC) is the commonest form of liver cancer in the world. Cancer chemoprevention using dietary supplements and phytochemicals has attracted increasing attention in recent years. Numerous study reports suggest the role of phytochemicals and dietary compounds in the prevention and treatment of liver cancer. Certain dietary agents and related phytochemicals present in grapes, pomegranate, vegetables, beans, turmeric, soy, rice bran, and fish oils are reported to have chemopreventive potentials against hepatocellular carcinoma. Phytochemicals such as Carotenoids, Epigallocatechin gallate (EGCG), Curcumin, Resveratrol, Rutoside, Quercetin, Chrysin and Silibinin have possible therapeutic importance in tumor suppression during the initial phases of carcinogenesis. Many phytochemicals which are still under investigation lack the scientific data in support of anticancer properties of these compounds rather than anti-oxidant mechanism. So, emphasis should be given on the investigation of plausible molecular mechanism behind anticancer activity. This review summarizes the use of these dietary agents and phytochemicals in the treatment and prevention of HCC and also highlights the mechanisms responsible for their effects. Med Phoenix Vol.2(1) July 2017, 52-62